Enhancing road safety of PLEVs by novel vehicle concepts: A comprehensive investigation on regulations, accident statistics, and perception of riders in Europe - Michelangelo-Santo Gulino; Susanna Papini; Giovanni Zonfrillo; Peter Miklis; Thomas Unger; Dario Vangi (Heliyon)
The rise of Personal Light Electric Vehicles (PLEVs), including electric bicycles and electric kick scooters, represents a relevant trend in current urban mobility. PLEVs offer economic, social, and environmental advantages, making them increasingly attractive for short-distance travel. Despite their benefits, concerns about the safety of PLEVs, particularly related to road accidents, have arisen due to their growing presence in urban areas.This paper examines various aspects of PLEV safety, focusing on equipment required by regulations, circulation aspects, and users' needs; based on such highlights, the objective is to derive a vehicle concept (in the form of a kick scooter) that integrates elements for PLEV safety maximization starting from the design phase. A review of PLEV-related regulation in European countries, and particularly for electric kick scooters, is initially provided to determine the mandatory equipment for their circulation in the widest possible number of countries. Analysis of accident data for PLEVs in the EU then reveals critical factors contributing to the occurrence of crashes, injuries, and casualties, as well as the type and severity of riders' injuries. Surveys on user perceptions shed light on safety concerns of daily riders, indicating the most relevant aspects to enhance from the user's perspective.Based on these findings, the study proposes a novel electric kick scooter concept integrating safety features derived from regulations, accident analysis, and user needs. Safety equipment aimed at increasing riding stability (high diameter wheel, pneumatic tyres) appears as the most promising solution for maximizing PLEV safety. Inclusion of turning light indicators can also increase riding stability, since the user can exhibit his/her intention of turning while maintaining the contact with the handlebar; as of today, this latter feature is mandatory only in Italy among all EU countries. The work additionally emphasizes the need for harmonized regulations, enhanced safety standards, specifically designed infrastructure, and user awareness campaigns to improve PLEV safety. This research is functional for the proposal of a sustainable and safe transportation solution that can increase the consensus towards PLEVs and the consequent spread of electric microvehicles.